Palaeoenvironmental evolution of the ancient lagoon of Ostia Antica (Tiber delta, Italy). (February 2015) - Vittori, Cecile; Mazzini, Ilaria; Salomon, Ferréol; Goiran, Jean-Philippe; Pannuzi, Simona; Rosa, Carlo; Pellegrino, Angelo
A bstract: The ancient lagoon of Ostia played a key role in the development of the cultures of central Italy and especially that of Rome. The evolution of its environmental history and its partial transformation into a saline body of water during Antiquity remain as poorly known to archaeologists and historians as to geologists and geographers. A high chronostratigraphical resolution palaeoenvironmental study has been carried out on a sediment core. It is based on multi-proxy analysis and pays particular attention to ostracods, which are very useful palaeoenvironmental indicators in marginal marine environments. Our study has unveiled five evolution phases of the landscapes in the countryside of Ostia: (1) between the 6th and the middle of the 2nd millennia BC a lagoon open to the sea was formed; (2) the lagoon was then subject to marine and fluvial influences, ; (3) between the middle of the 2nd and the beginning of the 1st millennia BC, a marshland formed, indicating either a period of limited flooding or a shifting of the branch of the Tiber; (4) during the first part of the 1st millennium BC, the lagoon became again connected to the sea. In this area, its depth at the time of the founding of Ostia varied between 3.5 m and 4.5 m (below ancient sea level), which suggests that it could have served as a naturally sheltered place on the coast; (5) from the middle of the 1st millennia BC to the 19th century AD, the lagoon probably remained connected to the sea and progressively silted, until it disappeared in the 19th century. Highlights: From mid. 1st m. BC to 19th c. AD: lagoon of Ostia remained connected to the sea. At the time of the founding of Ostia the depth of the lagoon was around 4 m. This geography and depth suggest that the lagoon could be a natural sheltered place. From mid. 1st m. BC: influence of the Tiber was much less significant in lagoon. Between the 2nd and the mid. 1st m. BC: lagoon of Ostia became a marshland.